The theology of nonviolence in the writings of Petr Chelčický during the late Middle Ages - Maíz, Jordi (2023)
The article explores the emergence of the Hussite movement and the establishment of egalitarian communities that embraced a lifestyle without taxes or private property. The concern of the authorities and the resulting internal conflicts highlighted significant changes and internal struggles. Leaders such as Jan Žižka adopted more aggressive and violent stances, considering Prague and other cities as enemies. In this context, Petr Chelčický, influenced by the Taborites, emerges as a prominent figure. His critical writings towards the clergy and the Church defend pacifism, egalitarianism, and communism, advocating for the autonomy of the Czech church and opposing German domination. Chelčický distances himself from the Hussites due to his rejection of violence and in his hometown, he develops an extensive body of work proposing a life free from materialism and power conflicts. His local influence is significant, leaving a legacy in the religious and social reforms of the era and beyond.